Ranking of important knowledge areas and measurement of competency levels of construction project managers in Cambodia - Jokkaw, Noppadon (Engineering and Applied Science Research, 2016)
The objectives of this paper are to rank the important knowledge and measure competency levels of construction Project Managers (PMs) in Cambodia. The important knowledge areas of construction PMs were analyzed and ranked by Analytic Hierarchy Process (AHP) method and competency levels were measured by Relative Level Index (RLI) from perception of main stakeholders such as contractors, consultants, and project owners. The results of ranking showed that time, quality, cost, and safety management are the main important knowledge areas for construction project managers in Cambodia, respectively. However, the ranking of important knowledge of contractor PMs is different among each stakeholder’s perception. Moreover, the result of competency level measurement presented that competency level of contractor PMs in Cambodia is in medium level. However, in perception of contractors, competency level of construction PMs in Cambodia is higher than competency level of contractor PMs in perception of consultants and project owners.